2016
DOI: 10.3390/s16111483
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Oxidase Biosensor Modeling and Predictors Optimization by Machine Learning Methods

Abstract: Biosensors are small analytical devices incorporating a biological recognition element and a physico-chemical transducer to convert a biological signal into an electrical reading. Nowadays, their technological appeal resides in their fast performance, high sensitivity and continuous measuring capabilities; however, a full understanding is still under research. This paper aims to contribute to this growing field of biotechnology, with a focus on Glucose-Oxidase Biosensor (GOB) modeling through statistical learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Estimation and visualization of spatio-temporal dynamics. The dynamics of water quality variables can be often hard to predict due to its very changing nature [ 24 , 25 ]. The spatio-temporal interpolation of measurements in different stations and in different campaigns has been previously shown not to be limited to a mere visualization, but instead it represents the estimation of the variable dynamics, which allows the researcher to get deep further knowledge into the relevant information conveyed in the already available data, such as temporal space trends or physical and chemical characteristics of pollutants that are closely related to environmental conditions and the geographical areas though which the stretches of the river circulate.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation and visualization of spatio-temporal dynamics. The dynamics of water quality variables can be often hard to predict due to its very changing nature [ 24 , 25 ]. The spatio-temporal interpolation of measurements in different stations and in different campaigns has been previously shown not to be limited to a mere visualization, but instead it represents the estimation of the variable dynamics, which allows the researcher to get deep further knowledge into the relevant information conveyed in the already available data, such as temporal space trends or physical and chemical characteristics of pollutants that are closely related to environmental conditions and the geographical areas though which the stretches of the river circulate.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al made use of convolutional neural network algorithms for colorimetric sensing of organic carbon in water [ 246 ]. Gonzalez et al provided a comparative analysis of various machine-learning algorithms for improving the accuracy of a glucose oxidase biosensor [ 247 ]. By using artificial neural networks and support-vector machine algorithms, Ali et al demonstrated successful impedance-based classification of Escherichia coli and Salmonella typhimurium by using silver nanowires on polyimide substrates [ 248 ].…”
Section: Nano-biosensors For Cancer Detection and Future Prospectimentioning
confidence: 99%
“…In recent years, various computational approaches have been employed in drug discovery and biosensor development. These encompass QSAR, virtual screening, molecular docking, homology modelling, and machine learning approaches ( Gonzalez-Navarro et al, 2016 ; Green et al, 2019 ). Some of these methods have their own advantages and drawbacks.…”
Section: Routes For Improvementmentioning
confidence: 99%